Effects of body angles on the aerodynamic characteristics in the flight period of ski jumping: a simulation study - Li, X.; Wang, X.; Chen, L.; Zhao, T. (Sports Biomechanics, 2023)
The flight period of ski jumping involves aerodynamic considerations. Reasonable controls and adjustments of in-flight body attitudes are beneficial to improve the aerodynamic performance of athletes, thus obtaining a longer flight distance. Here, the aerodynamic forces and moments of a simplified body-ski model in the flight period are calculated via the computational fluid dynamics (CFD) method, considering influences of head angle, hip angle, and body-ski angle, and the contributions of each body part are discussed. Results show that the hip angle and body-ski angle dominate the aerodynamic performance, and the skis and the trunk contribute most to the aerodynamic force and moment. In addition, based on CFD results, the hip angle and body-ski angle are selected as design variables, and optimisations for lift area and lift-to-drag ratio are conducted via the combination of Kriging models and genetic algorithm. When the lift-to-drag ratio reaches its peak (which is beneficial to the early flight), the athlete should keep a flatter body attitude, leading to a relatively low lift area and drag area. Properly raising the posture of the body can get a higher lift area, which is beneficial to balance the gravity and prolong the athletes` flight distance in the late flight.